The effect of milk quota abolishment on farm intensity: Shifts and stability. (1st June 2016) - Groeneveld, Anouschka; Peerlings, Jack; Bakker, Martha; Heijman, Wim
Highlights: A mathematical programming model is applied to the Dutch dairy sector. The milk quota abolition and associated policy measures are analysed. The number of cows will increase for most of the farm types. Only farms that are large in terms of Standard Output will become very intensive. Abstract: We investigate whether milk quota abolition in the Netherlands is likely to lead to a shift towards more intensive farms, and whether the legislation introduced by the Dutch government to prevent this from happening is likely to be effective. To this end, a mathematical programming model is developed and applied to ten Dutch dairy farms of varying size. The mathematical programming model allows us to calculate shadow prices, which we use to evaluate the stability or likelihood of a shift in the farmer decisions in our model. Our results suggest a strong increase in intensity for the largest farm type when milk quotas are abolished, while further intensification is limited for the smaller farm types. Although most farm types increase the number of cows on the farm, for the smaller ones this can only be achieved when the costs of expanding decrease considerably. The new legislation introduced by the Dutch government to prevent strong intensification appears to be successful.